Update Terkini Endometriosis: Patofisiologi, Dampak Fertilitas, Kualitas Hidup, dan Penatalaksanaan - Zahra Rantika; Ajeng Ramadani; Lara Lara; Harmy Hapsari; Rachel Zahwa Alyscha Alfaerhie; Yeti Mareta Undaryati (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
Endometriosis is a chronic, estrogen-dependent inflammatory disease defined by the presence of endometrium-like tissue growing outside the uterine cavity. Affecting an estimated 6–15% of women of reproductive age worldwide, the condition is frequently diagnosed with a delay exceeding a decade from symptom onset. This review synthesizes current scientific evidence on the pathophysiology, inflammatory mechanisms, causative factors, and the impact of endometriosis on female fertility and psychosocial wellbeing, while also examining emerging management strategies. A systematic literature search was conducted across PubMed, Medline, Embase, the Cochrane Library, and Web of Science, selecting full-text English-language articles published between 2021 and 2025. Findings indicate that endometriosis is not merely a localized pelvic disorder but a systemic neuro-inflammatory syndrome whose pathogenesis encompasses retrograde menstruation, estrogen dominance, progesterone resistance, and epigenetic dysregulation involving DNA methylation, histone modification, and microRNA dysregulation. Fertility impairment occurs through layered mechanisms including pelvic adhesion formation, reduced oocyte quality, and implantation failure, while persistent chronic pain drives clinically significant depression, anxiety, and productivity loss. Promising current management approaches include combined hormonal therapy, molecular-targeted agents, and structured physical activity programs demonstrated to improve patient quality of life. This review concludes that endometriosis management requires a multidisciplinary strategy oriented toward fertility preservation and long-term quality of life improvement.